Answers

The Brainliest Answer!
2014-09-12T13:16:28+05:30
The common denominator is 6.

So we will multiply the first fraction with 3
the 1 will be multiplied with 6
and the result with 2.

In this way we will get rid of the fraction.
3(6y+1)+1*6=2(7y-3)
18y+3+6=14y-6
18y+9=14y-6
18y-14y=-6-9
4y=-15
y=-15/4


3 3 3
welcome
but i didn't understand the word amplify in the second question
please kindly elaborate , please
done. Now it's clear?
yes. it is thank you : )
2014-09-12T13:28:21+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
\frac{6y+1}{2} + 1 = \frac{7y-3}{3}

\frac{6y+1 +2}{2}= \frac{7y-3}{3}

\frac{6y+3}{2}= \frac{7y-3}{3}

{3(6y+3)}= {2(7y-3)}

18y+9 =14y - 6\\

4y = -15

y=\frac{-15}{4}
2 5 2
you will refresh the page
it did but by mistake i did it to someone else :(
ok no prob
thank you, and sorry
come to private chat